2020
DOI: 10.21037/med.2019.09.06
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted mediastinoscopic lymphadenectomy (VAMLA) for staging & treatment of non-small cell lung cancer (NSCLC)

Abstract: Precise preoperative staging and restaging of mediastinal lymph nodes in patients with potentially resectable non-small cell lung cancer (NSCLC) is of supreme importance. Over the last years, algorithms on preoperative mediastinal staging incorporating imaging, endoscopic and surgical techniques have been widely published, offering more evidence concerning different mediastinal staging techniques. Current guidelines well define when and how to receive tissue confirmation in case of computed tomography (CT)-enl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…The authors concluded that confirmatory mediastinoscopy can be omitted in patients with resectable NSCLC, also reducing delays in treatment. Based on these considerations, the use of video-assisted mediastinoscopic lymphadenectomy (VAMLA) or transcervical extended mediastinal lymphadenectomy (TEMLA) [ 19 , 20 ] does not appear justified due to the continuous search for minimally invasive diagnostic and surgical approaches; hence, the need for a re-evaluation of the indications is imperative in order to tailor the procedures on each patient. This concept is stressed by Mullins et al [ 21 ] regarding early-stage inoperable NSCLC patients, who underwent stereotactic body radiotherapy (SBRT) after CT-guided needle biopsy (Group 1: 79 patients) and navigational bronchoscopy with EBUS for hilar and mediastinal staging (Group 2: 79 patients).…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that confirmatory mediastinoscopy can be omitted in patients with resectable NSCLC, also reducing delays in treatment. Based on these considerations, the use of video-assisted mediastinoscopic lymphadenectomy (VAMLA) or transcervical extended mediastinal lymphadenectomy (TEMLA) [ 19 , 20 ] does not appear justified due to the continuous search for minimally invasive diagnostic and surgical approaches; hence, the need for a re-evaluation of the indications is imperative in order to tailor the procedures on each patient. This concept is stressed by Mullins et al [ 21 ] regarding early-stage inoperable NSCLC patients, who underwent stereotactic body radiotherapy (SBRT) after CT-guided needle biopsy (Group 1: 79 patients) and navigational bronchoscopy with EBUS for hilar and mediastinal staging (Group 2: 79 patients).…”
Section: Discussionmentioning
confidence: 99%
“…We have to bring 2 aspects to mind: (1) the ancient but still present definition of an N3-status meaning surgically not accessible and (2) it is becoming increasingly clear that the percentage of positive lymph nodes (the so called "node ratio") depict the clinically relevant tumor stadium more accurate than the anatomical N2/3 categorization. [14][15][16][17][18][19][20] Both keynotes will be translated into the upcoming 9th edition of the Union for International Cancer Control staging system for lung cancer-as well as being basis for ongoing research as clinical investigators increasingly lift out the lively character of a tumor instead of its strict compartmentation. So after more than 60 years of great facility and constant advancements the golden age of up-to-date mediastinoscopy-which is called VAMLA for nearly 20 years-is not over for a long time yet.…”
Section: Discussionmentioning
confidence: 99%
“…EBUS and EUS are complementary techniques that allow for visualization and biopsy of most of the mediastinal nodes [14]. Notably, TEMLA, a relatively novel technique involving the complete removal of the mediastinal nodes and surrounding adipose tissue, aims to enhance the accuracy of NSCLC staging and restaging after neoadjuvant treatment [10,15,16].…”
Section: Introductionmentioning
confidence: 99%